Molecular cloning and biotic elicitation response of phenylalanine ammonia-lyase gene of Astragalus chrysochlorus - Turgut Kara, Neslihan; í‡akır, í–zgür; Arıkan, Burcu; Arı, Åžule (Cellular and Molecular Biology, 2018)
Phenylalanine ammonia lyase (PAL) is the first enzyme of the phenylpropanoid pathway, and it is necessary to upregulate flavonoid biosynthesis in most of the plant species. In this study, we have cloned PAL gene from endemic Astragalus chrysochlorus which is a producer of phenolic nicotiflorin (kaempferol-3-O-rutinoside). The cDNA encoding PAL was cloned from A. chrysochlorus using RT-PCR (reverse transcription-polymerase chain reaction) with conserved primer pairs. Amino acid sequence alignments showed that AcPAL (2160 bp, Accession number: KM189182) has more than 95% amino acid identity with their homologues in other Astragalus species. The coding sequence for the protein of AcPAL is 720 amino acids with a calculated molecular weight of 78.53 kDa. Full length AcPAL was cloned and expressed in Escherichia coli. qPCR (quantitative real-time PCR) analysis of the expression of PAL gene of A. chrysochlorus suggested that maximum transcript level was observed in 3 h yeast extract elicited suspension cells. Our findings suggest that AcPAL plays role in early response for yeast extract treatment. The isolation of AcPAL gene could be result in further studies for overproduction of secondary metabolite, nicotiflorin.